2007
DOI: 10.1183/09031936.00154006
|View full text |Cite
|
Sign up to set email alerts
|

Increased airway iron as a potential factor in the persistence of Pseudomonas aeruginosa infection in cystic fibrosis

Abstract: Iron availability is critical to many bacteria and increased iron has been described in airway secretions in cystic fibrosis (CF). The main aim of the present study was to assess the relationship between iron in CF sputum and the quantitative bacterial burden.Iron, ferritin and total cell counts (TCC) were assessed in sputum samples obtained from 15 clinically stable CF patients chronically infected with Pseudomonas aeruginosa. Sputum samples were also obtained at the commencement of episodes of acute exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(153 citation statements)
references
References 28 publications
(34 reference statements)
8
140
2
Order By: Relevance
“…Furthermore, iron and ferritin levels are positively correlated with c.f.u. of P. aeruginosa and remain elevated after antibiotic treatment of P. aeruginosa infection (Reid et al, 2007). Aspergillus fumigatus co-cultured with macrophages downregulates expression of two cellular iron importers and the iron exporter ferroportin, which, together with an increase in iron retention and ferritin synthesis by the exposed macrophages, provides further evidence of the impact of infection on host iron homeostasis (Seifert et al, 2008).…”
Section: Iron and Cfmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, iron and ferritin levels are positively correlated with c.f.u. of P. aeruginosa and remain elevated after antibiotic treatment of P. aeruginosa infection (Reid et al, 2007). Aspergillus fumigatus co-cultured with macrophages downregulates expression of two cellular iron importers and the iron exporter ferroportin, which, together with an increase in iron retention and ferritin synthesis by the exposed macrophages, provides further evidence of the impact of infection on host iron homeostasis (Seifert et al, 2008).…”
Section: Iron and Cfmentioning
confidence: 86%
“…In a recent study of CF pulmonary exacerbation, patients following treatment with intravenous antibiotics had lower hepcidin and IL-6 levels in serum, increased serum iron, and a trend towards lower sputum iron levels -further evidence of the impact of infection and inflammation on iron metabolism (Gifford et al, 2012). Not surprisingly, given the inflammatory environment of the CF lung, elevated levels of iron and ferritin have been detected in CF sputum by a number of studies (Stites et al, 1998(Stites et al, , 1999Reid et al, 2004Reid et al, , 2007Gray et al, 2010). More recently in a comprehensive study of iron in CF, Ghio et al (2013) demonstrated increased levels of iron and iron-related proteins in bronchoalveolar lavage fluids from CF children, in macrophages of explanted CF lungs and in lung tissue from CF patients -clear evidence of altered iron homeostasis and of iron accumulation in the CF airways (Ghio et al, 2013).…”
Section: Iron and Cfmentioning
confidence: 99%
“…Ferritin is an acute-phase reactant with clinical implications as a serologic marker of acute and chronic inflammation. It often increases during periods of oxidative stress such as acute respiratory distress syndrome (ARDS) 22,23 or cystic fibrosis 24 for the detoxification of free iron, because free iron facilitates the formation of highly toxic hydroxyl radicals from hydrogen peroxide. 25,26 In addition, polymorphisms within the gene that encodes the ferritin light chain are associated with the development of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is not freely available to infectious bacteria in the healthy human airway, because it is predominantly assimilated into iron-binding proteins such as transferrin, lactoferrin, and ferritin, but larger amounts of iron are present in CF lungs (6)(7)(8). Iron in biological environments is commonly present as ferric (Fe 3ϩ ) ions, although the reduced pH (9) and the poor availability of O 2 in the thick mucus layers of CF airways (10,11) may mean that significant amounts of ferrous (Fe 2ϩ ) iron are present.…”
Section: T He Thick Viscous Mucus In the Lungs Of Cystic Fibrosis (Cmentioning
confidence: 99%